PENGARUH PENDIDIKAN KARAKTER SISWA SEKOLAH TERHADAP PRESTASI BELAJAR SISWA DI SMPN 19 BEKASI - Husaini, Alfi; Fadilah, Hudzaifah Akmal; Diningsih, Ayu; Putra, Purnama (Jurnal Kinerja, 2025)
This study aims to examine the influence of character education on the academic achievement of seventh-grade students at SMPN 19 Bekasi during the 2022/2023 academic year. The research is grounded in the importance of character values such as discipline, responsibility, and honesty in supporting students’ academic success. A quantitative approach was employed using an experimental method and quota sampling technique involving 31 students. The instruments utilized in this study were questionnaires and academic achievement tests, which were analyzed using validity, reliability, normality, and simple regression tests with the assistance of SPSS version 21. The results indicate a significant relationship between character education and students’ academic achievement, as evidenced by a correlation coefficient value of 0.574, categorized as a moderately strong relationship. The collected data were normally distributed, and the research instruments were both valid and reliable. These findings reinforce moral development theory and are consistent with previous studies that emphasize the positive contribution of character education to students’ academic performance. Therefore, character education should be integrated into the learning process and supported by the active involvement of families and the broader community.